2015
DOI: 10.1176/appi.ps.201400051
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Outpatient Care From Psychiatrists: A Simulated-Patient Study in Three U.S. Cities

Abstract: Obtaining outpatient appointments with psychiatrists in three cities was difficult, irrespective of payer. RESULTS suggest that expanding insurance coverage alone may do little to improve access to psychiatrists-or worse, expansion might further overwhelm the capacity of available services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 7 publications
3
39
0
Order By: Relevance
“…Among the 230 psychiatrists who have clinical practices in Vancouver, only 6 were available to provide a consultation in a timely manner. This study 15 has been replicated in the United States with very similar findings. Finally, a recent study 16 of regional psychiatrist supply and associated practice patterns in Ontario revealed that as the number of psychiatrists increases regionally, the average psychiatrist's outpatient volume decreases.…”
supporting
confidence: 67%
“…Among the 230 psychiatrists who have clinical practices in Vancouver, only 6 were available to provide a consultation in a timely manner. This study 15 has been replicated in the United States with very similar findings. Finally, a recent study 16 of regional psychiatrist supply and associated practice patterns in Ontario revealed that as the number of psychiatrists increases regionally, the average psychiatrist's outpatient volume decreases.…”
supporting
confidence: 67%
“…After two rounds of phone calls 2 weeks apart, more than one half of 360 psychiatrists could not be reached or were not taking new patients. 16 Appointments could be obtained with only 93 (26%), with an average additional wait of 25 days. 16 The overall scarcity of psychiatrists is magnified when seeking a psychiatrist trained in managing patients with medical illness and comorbid psychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%
“…16 Appointments could be obtained with only 93 (26%), with an average additional wait of 25 days. 16 The overall scarcity of psychiatrists is magnified when seeking a psychiatrist trained in managing patients with medical illness and comorbid psychiatric disorders. However, there are several limitations that influence the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 This also appears to be the case in large American cities. 23 Moreover, private offices do not encourage consultation-liaison or collaboration with first-line services and with other health professionals. Instead of extending the reach of the specialist through shared care, 24 the private office can easily become a bunker that is inaccessible to the community.…”
Section: Beyond Office Practicementioning
confidence: 99%